Intertwining DNA-RNA nanocapsules loaded with tumor neoantigens as synergistic nanovaccines for cancer immunotherapy. Issue 1 (December 2017) - Zhu, Guizhi; Mei, Lei; Vishwasrao, Harshad; Jacobson, Orit; Wang, Zhantong; Liu, Yijing; Yung, Bryant; Fu, Xiao; Jin, Albert; Niu, Gang; Wang, Qin; Zhang, Fuwu; et al.
Abstract Nanomedicines that co-deliver DNA, RNA, and peptide therapeutics are highly desirable yet remain underdeveloped for cancer theranostics. Herein, we report self-assembled intertwining DNA-RNA nanocapsules (iDR-NCs) that efficiently delivered synergistic DNA CpG and short hairpin RNA (shRNA) adjuvants, as well as tumor-specific peptide neoantigens into antigen presenting cells (APCs) in lymph nodes for cancer immunotherapy. These nanovaccines were prepared by (1) producing tandem CpG and shRNA via concurrent rolling circle replication and rolling circle transcription, (2) self-assembling CpG and shRNA into DNA-RNA microflowers, (3) shrinking microflowers into iDR-NCs using PEG-grafted cationic polypeptides, and (4) physically loading neoantigen into iDR-NCs. CpG and shRNA in iDR-NCs synergistically activate APCs for sustained antigen presentation. Remarkably, iDR-NC/neoantigen nanovaccines elicit 8-fold more frequent neoantigen-specific peripheral CD8+ T cells than CpG, induce T cell memory, and significantly inhibit the progression of neoantigen-specific colorectal tumors. Collectively, iDR-NCs represent potential DNA/RNA/peptide triple-co-delivery nanocarriers and synergistic tumor immunotherapeutic nanovaccines. Nucleic acid nanomedicines are promising for cancer drug delivery. Here, the authors show using a mouse model the tumor immunotherapeutic efficacy of nanovaccines based on intertwining DNA-RNA nanocapsules loaded with DNA CpG, Stat3 -silencing short hairpin RNA and tumor-specific peptide neoantigens.